1995
DOI: 10.1037/0022-006x.63.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Resolving "unfinished business": Efficacy of experiential therapy using empty-chair dialogue.

Abstract: In this study, 34 clients with unresolved feelings related to a significant other were randomly assigned to either experiential therapy using a Gestalt empty-chair dialogue intervention or an attention-placebo condition. The latter was a psychoeducational group offering information about "unfinished business." Treatment outcomes were evaluated before and after the treatment period in each condition and at 4 months and 1 year after the experiential therapy. Outcome instruments targeted general symptomotology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
150
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 188 publications
(159 citation statements)
references
References 21 publications
7
150
1
1
Order By: Relevance
“…Effect sizes were substantial and comparable to those reported in other successful treatment outcome studies (Lambert & Bergin, 1994). Results of the present study replicate and extend previous findings (Paivio & Greenberg, 1995) on the efficacy of experiential therapy for resolving interpersonal issues from the past. EFT-AS was based on the same model of therapy, refined and tailored to a particular client group (Paivio & Shimp, 1998).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Effect sizes were substantial and comparable to those reported in other successful treatment outcome studies (Lambert & Bergin, 1994). Results of the present study replicate and extend previous findings (Paivio & Greenberg, 1995) on the efficacy of experiential therapy for resolving interpersonal issues from the past. EFT-AS was based on the same model of therapy, refined and tailored to a particular client group (Paivio & Shimp, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…Measurable steps in the process that discriminated resolvers from nonresolvers were expression of emotion and unmet need, and changed perceptions of self and other (Greenberg & Foerster, 1996). A shortterm treatment based on this model of resolution was found to be effective with a general clinical population (Paivio & Greenberg, 1995). That sample included a subgroup of individuals who were dealing with child abuse issues.…”
mentioning
confidence: 99%
“…In chair-work, the patient switches between chairs and is invited to have dialogues between different parts of the self (Kellogg, 2004;Paivio & Greenberg, 1995). The patient sits in one chair when he plays a certain mode and switches chairs when a different mode is addressed or becomes active.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…For example, Paivio and Greenberg (1995) found that in outpatients (N = 34; selected for interpersonal problems and clinically judged appropriateness for psychotherapy), affiliation improved more after 3 months of experiential therapy than of psychoeducation (a control condition). In the experiential therapy group, treatment gains were maintained at a 4 month follow-up but were no longer significant at a 1-year follow-up.…”
mentioning
confidence: 99%